"Get lucky!" Sexual content in music lyrics, videos and social media and sexual cognitions and risk among emerging adults in the USA and Australia. Issue 1 (2nd January 2017) - Wright, Chrysalis L.; Rubin, Mark
Abstract: This study examined the relationship between sexual content in music and sexual cognitions and risk among emerging adults in the USA and Australia. Music content was examined via lyrics, videos and social media. It was hypothesised that there would be a positive association between sexual content in music and sexual cognitions and risk. Sexual content in music lyrics, videos, and social media was assessed using content analysis of the top artists rated by participants in the USA and Australia. Findings indicated variations in sexual content based on music genre and location, and that music lyrics, videos and social media all contain sexual content. Results from hierarchical regression analyses indicated that sexual lyrical content, sexual content in music videos, and sexual references in the social media posts of artists were related to negative sexual cognitions for both samples. This trend was also found for the degree of sexual risk for both samples. While findings point to the direction of a universal impact of the association between sexual content in music and sexual cognitions and degree of sexual risk, they also highlight trends in these relationships across countries.